Biomarkers for the Clinical Diagnosis of Alzheimer’s Disease: Metabolomics Analysis of Brain Tissue and Blood - Wang, Yang-Yang; Sun, Yan-Ping; Luo, Yu-Meng; Peng, Dong-Hui; Li, Xiao; Yang, Bing-You; Wang, Qiu-Hong; Kuang, Hai-Xue (Frontiers in Pharmacology, 2021)
With an increase in aging populations worldwide, age-related diseases such as Alzheimer’s disease (AD) have become a global concern. At present, a cure for neurodegenerative disease is lacking. There is an urgent need for a biomarker that can facilitate the diagnosis, classification, prognosis, and treatment response of AD. The recent emergence of highly sensitive mass-spectrometry platforms and high-throughput technology can be employed to discover and catalog vast datasets of small metabolites, which respond to changed status in the body. Metabolomics analysis provides hope for a better understanding of AD as well as the subsequent identification and analysis of metabolites. Here, we review the state-of-the-art emerging candidate biomarkers for AD.